Ip man. Kung fu master [videorecording (DVD)] - Li, Liming; Du, Yuhang; Guangliang, 1970- (Magnolia Home Entertainment, 2021)
During his time as a police captain in Foshan, Ip Man is targeted by a vengeful gangster just as the Japanese army invades the region.